Infusion Reactions After Receiving the Broadly Neutralizing Antibody VRC01 or Placebo to Reduce HIV-1 Acquisition: Results From the Phase 2b Antibody-Mediated Prevention Randomized Trials. (1st April 2022) - Takuva, Simbarashe; Karuna, Shelly T.; Juraska, Michal; Rudnicki, Erika; Edupuganti, Srilatha; Anderson, Maija; De La Grecca, Robert; Gaudinski, Martin R.; Sehurutshi, Alice; Orrell, Catherine; Naidoo, Logashvari; Valencia, Javier; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: The antibody-mediated prevention (AMP) studies (HVTN 703/HPTN 081 and HVTN 704/HPTN 085) are harmonized phase 2b trials to assess HIV prevention efficacy and safety of intravenous infusion of anti-gp120 broadly neutralizing antibody VRC01. Antibodies for other indications can elicit infusion-related reactions (IRRs), often requiring premedication and limiting their application. We report on AMP study IRRs. Methods: From 2016 to 2018, 2699 HIV-uninfected, at-risk men and transgender adults in the Americas and Switzerland (704/085) and 1924 at-risk heterosexual women in sub-Saharan Africa (703/081) were randomized 1:1:1 to VRC01 10 mg/kg, 30 mg/kg, or placebo. Participants received infusions every 8 weeks (n = 10/participant) over 72 weeks, with 104 weeks of follow-up. Safety assessments were conducted before and after infusion and at noninfusion visits. A total of 40, 674 infusions were administered. Results: Forty-seven participants (1.7%) experienced 49 IRRs in 704/085; 93 (4.8%) experienced 111 IRRs in 703/081 ( P < 0.001). IRRs occurred more frequently in VRC01 than placebo recipients in 703/081 ( P < 0.001). IRRs were associated with atopic history ( P = 0.046) and with younger age ( P = 0.023) in 703/081. Four clinical phenotypes of IRRs were observed: urticaria, dyspnea, dyspnea with rash, and "other." Urticaria was most prevalent, occurring in 25 (0.9%) participants in 704/085 and 41 (2.1%) participants in 703/081. Most IRRs occurred with the initial infusion and incidence diminished through the last infusion. All reactions were managed successfully without sequelae. Conclusions: IRRs in the AMP studies were uncommon, typically mild or moderate, successfully managed at the research clinic, and resolved without sequelae. Analysis is ongoing to explore potential IRR mechanisms.